بناء مقياس التجول العقلي لطالبات كلية التربية الرياضية جامعة حلوان - المرسى، مني مختار; مصطفى، غادة فاروق عبدالعزيز; عبدالعاطي، الزهراء حمدي (جامعة حلوان - كلية التربية الرياضية للبنات, 2024)
يهدف البحث إلى بناء مقياس التجول العقلي لطالبات كلية التربية الرياضية جامعة حلوان، التي يتراوح أعمارهن ما بين (۱۹ - ۲۲ سنة)، تم استخدام المنهج الوصفي بخطوات وإجراءات لملائمته طبيعة البحث، واختير مجتمع البحث من طالبات الفرق الأربعة بكلية التربية الرياضية للبنات جامعة حلوان للعام الدراسي 2023/2024 عددهن وقوامهن ۲۰۲۰ طالبة، بواقع (٣٢٥) طالبة للفرقة الأولى، (٦١٥) طالبة للفرقة الثانية، (٢٧٦) طالبة للفرقة الثالثة، (٨٠٤) طالبة للفرقة الرابعة، تم اختيار عينة البحث الاستطلاعية بالطريقة العشوائية وقوامها ۷۰ طالبة من طالبات الفرق الأربعة بكلية التربية الرياضية للبنات جامعة حلوان بغرض حساب المعاملات العلمية للمقياس. تكون مقياس التجول العقلي في صورته المبدئية من محوران (التجول العقلي المرتبط بموضوع المحاضرة، التجول العقلي الغير مرتبط بموضوع المحاضرة) و٦٩ عبارة وبعد العرض على الخبراء أصبح المقياس مكون ٤٢ عبارة بعد استبعاد العبارات التي حذفت من خلال صدق الاتساق الداخلي، وأصبحت الصورة النهائية مكونة من المحور الأول ٢٦ عبارة والمحور الثاني ١٦ عبارة، وتم وضع ميزان تقدير ثلاثي (دائماً، أحياناً، أبداً)، ودرجتها على التوالي (۱، ۲، ۳). The research aims to build a measure of mental wandering for female students of the Faculty of Physical Education, Helwan University, whose ages range between (19 -22 years). The descriptive approach was used with steps and procedures to suit the nature of the research. The research community was chosen from the students of the four teams at the Faculty of Physical Education for Girls, Helwan University, for the academic year. 2023/2024 Their number and strength are 2020 female students, with (325) female students for the first year, (615) female students for the second year, (276) female students for the third year, (804) female students for the fourth year. The exploratory research sample was chosen randomly and consists of 70 female students from the four teams in the college. Physical education for girls, Helwan University, for the purpose of calculating the scientific coefficients of the scale. The mental wandering scale in its initial form consisted of two axes (mental wandering related to the lecture topic, and mental wandering not related to the lecture topic) and 69 phrases. After presenting it to the experts, the scale became composed of 42 phrases after excluding the phrases that were deleted through the validity of internal consistency, and the final form became composed of the axis. The first axis has 26 phrases, and the second axis has 16 phrases. A three-point rating scale has been developed (always, sometimes, never), and their scores are respectively (3, 2, 1).
Keywords: التجول العقلي -- طلبة الجامعات -- التربية الرياضية -- العملية التعليمية